Team handball match analysis by computer tracking from the men´s european championships 2016 - Michalsik, L. B.; Søndergaard, H.; Flynn, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Using time-motion analysis in team handball (TH) has some limitations, since this analysing method is influenced by subjective assessments and does not actually measure the precise locomotion speed. Now a new analysing system has been developed by Prozone Sports, which measures the actual locomotion speed of the players, and in addition can account for all changing actions, i.e. accelerations and decelerations, that occur during match-play even when the speed is low. Methods: The activity pattern of top international male elite TH players were evaluated by computer tracking at the men´s European Championships 2016 in Poland during matches in the main round. The matches were recorded using a three camera setup (Baumer TXG13c) in order to gain full coverage of the TH court. The three videos were independently tracked to produce trajectories and events for each individual player based on the video images. As a result the players are not required to wear a device, and the system is able to capture both playing teams. The player`s oncourt coordinates are then analysed by quality control operators to verify the player trajectories and events. Finally, software quantifies the locomotion and technical variables for each player and team. Results: The mean total playing time (TPT) per match for all players (n=136) including all stoppages, but excluding the half-time break, was 77.12±3.11 min (group means±SD), corresponding to 28.5 % extension compared to the normal effective match time of 60 min. In average, wing players (WP) played longer (50.46±23.39 min~65.4% of TPT, p<0.05) than goalkeepers (G: 42.60±28.55 min~55.2%), pivots (PV: 35.11±20.65 min~45.5%) and backcourt players (BP: 34.27±20.25 min~44.4%), respectively. The mean total distance covered (TDC) for field players (FP, n=118) was 2915±1662 m with a mean playing time of 38.40±22.23 min (~49.8% of TPT, range: 0.9-80.4 min). WP covered a longer mean total distance (3987±1778 m, p<0.05) than the other playing positions (BP: 2574±1491 m; PV: 2562±1363 m, G: 1550±1077 m). For FP with long on-court playing time (61.80±10.52 min~80.1% of TPT), TDC per match was 4625±863 m. High-intensity running (HIR) constituted only 1.8±1.0 % of TPT corresponding to 8.8±4.6 % of TDC. However, in relation to the total effective playing time of 60 min, HIR constituted for FP 2.5±1.3% and was higher for WP (4.2±2.8 %, p<0.05) compared to the other playing positions (PV: 2.1±3.8 %; BP: 1.6±2.9 %, G: 0.02±0.2 %). Furthermore, FP performed a mean of 76±124 accelerations and 66±105 decelerations when the speed was low, where WP performed the highest number compared to all other playing positions (102±117, 86±112, p<0.05). Conclusions: Match analysis by computer tracking showed that male top international elite TH imposes moderate-to-high demands on the aerobic energy system and very high demands on the anaerobic energy systems during certain periods of the match. The activity pattern differed markedly between playing positions, with WP showing a more intense locomotion activity profile than BP, PV and G.